A Comparative Study for Sonic Spray and Electrospray Ionization Methods to Determine Noncovalent Protein–Ligand Interactions. (2nd November 2019) - Ozdemir, Abdil; Gulfen, Mustafa; Lin, Jung-Lee; Chen, Chung-Hsuan
Abstract: A comparative study between sonic spray ionization (SSI) and electrospray ionization (ESI) is reported for cluster formation of proteins and ligands. For the observation of cluster formation, the interactions were not classified as specific or nonspecific and the instrumental parameters were held constant for both ion sources. Although ESI is a soft ionization method, it induces the formation of additional cluster formation between the protein–ligand couples. To understand this phenomenon, similar experiments were conducted using the same conditions by SSI. The equilibrium constants ( Kd ) of these complexes were calculated from the measurements obtained using both SSI and ESI. It is a common belief that SSI follows the charge residue model (CRM) and should form higher numbers of clusters. In the selected cases, although CRM is mostly followed, it does not give the same results in some specific situations. ESI produces more clusters during the ionization process for cytochrome-c maltoheptaose. The dependences of concentration, voltage and pH upon the complex formation were determined and number of maltoheptaose molecules bound were compared for both SSI and ESI sources. The main reason for the higher cluster formation is the applied voltage to the ESI source. High or low voltage causes distortion of globular structure of the proteins that leads to the formation of more clusters in the ESI source.